Control balance behind bars: testing the generality of tittle’s theory among incarcerated men and women - Fox, Kathleen A. (Crime & delinquency, 2016)
The current study contributes to the small, but growing, body of literature testing Tittle’s control balance theory by offering a unique test of the theory’s ability to explain a wide variety of offending among a large sample of recently incarcerated jail inmates. Among the full sample of inmates, both control deficits and surpluses significantly increase the risk of offending. When men and women are examined separately, control deficits are non-significant while control surpluses continue to increase offending, and this effect does not significantly vary among men and women. Evidence from the interactive effects of control imbalance and self-control indicate that control surpluses and low self-control are also related to committing a wider variety of crimes.